High-performance coaxial wire-shaped supercapacitors using ionogel electrolyte toward sustainable energy system. Issue 17 (16th September 2019) - Liu, Yongchao; Narayanasamy, Mugilan; Yang, Cheng; Shi, Minjie; Xie, Wei; Wu, Hanzhao; Yan, Chao; Hou, Hua; Guo, Zhanhu
Abstract: Abstract : Wire-shaped supercapacitors (WSSCs) hold great promise in portable and wearable electronics. Herein, a novel kind of high-performance coaxial WSSCs has been demonstrated and realized by scrolling porous carbon dodecahedrons/Al foil film electrode on vertical FeOOH nanosheets wrapping carbon fiber tows (FeOOH NSs/CFTs) yarn electrode. Remarkably, ionogel is utilized as solid-state electrolyte and exhibits a high thermal/electrochemical stability, which effectively ensures the great reliability and high operating voltage of coaxial WSSCs. Benefiting from the intriguing configuration, the coaxial WSSCs with superior flexibility act as efficient energy storage devices and exhibit low resistance, high volumetric energy density (3.2 mW h/cm 3 ), and strong durability (82% after 10, 000 cycles). Importantly, the coaxial WSSCs can be effectively recharged by harvesting sustainable wind source and repeatedly supply power to the lamp without a decline of electrochemical performance. Considering the facile fabrication technology with an outstanding performance, this work has paved the way for the integration of sustainable energy harvesting and wearable energy storage units.